2011
DOI: 10.1159/000331235
|View full text |Cite
|
Sign up to set email alerts
|

The Phonetic Manifestation of French /s#∫/ and /∫#s/ Sequences in Different Vowel Contexts: On the Occurrence and the Domain of Sibilant Assimilation

Abstract: While assimilation was initially regarded as a categorical replacement of phonemes or phonological features, subsequent detailed phonetic analyses showed that assimilation actually generates a wide spectrum of intermediate forms in terms of speech timing and spectrum. However, the focus of these analyses predominantly remained on the assimilated speech sound. In the present study we go one step ahead in two ways. First, we look at acoustic phonetic detail that differs in the French vowels /i, a, u/ preceding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The alveolar fricative /s/ has been shown to have more coarticulation resistance than /t/ (Recasens et al, 1997;Stone, Faber, Raphael, & Shawker, 1992), due to an additional constraint on the lateral margins of the tongue for the fricative production. On the other hand, / Ð / has been demonstrated to be more resistant than /s/ (Niebuhr & Meunier, 2011;Pouplier, Hoole, & Scobbie, 2011;Recasens & Espinosa, 2009;Tabain, 2001;Zharkova, Hewlett, & Hardcastle, 2012;Zharkova, Hewlett, Hardcastle, & Lickley, 2014a), likely due to the biomechanical properties of the tongue dorsum, specifically its mass and inertia (Recasens & Espinosa, 2010). In this study, vowel-related coarticulation on / Ð /, /s/, /t/ and /p/ was analysed, and we expected to observe consonant-specific differences according to the DAC model predictions.…”
Section: Introductionmentioning
confidence: 84%
“…The alveolar fricative /s/ has been shown to have more coarticulation resistance than /t/ (Recasens et al, 1997;Stone, Faber, Raphael, & Shawker, 1992), due to an additional constraint on the lateral margins of the tongue for the fricative production. On the other hand, / Ð / has been demonstrated to be more resistant than /s/ (Niebuhr & Meunier, 2011;Pouplier, Hoole, & Scobbie, 2011;Recasens & Espinosa, 2009;Tabain, 2001;Zharkova, Hewlett, & Hardcastle, 2012;Zharkova, Hewlett, Hardcastle, & Lickley, 2014a), likely due to the biomechanical properties of the tongue dorsum, specifically its mass and inertia (Recasens & Espinosa, 2010). In this study, vowel-related coarticulation on / Ð /, /s/, /t/ and /p/ was analysed, and we expected to observe consonant-specific differences according to the DAC model predictions.…”
Section: Introductionmentioning
confidence: 84%
“…On the other hand, research on assimilatory processes, in particular in /s#ʃ/ or /ʃ#s/ across word boundaries, has shown that sibilants vary gradually between the two places of articulation depending on the degree of assimilation (Niebuhr et al, 2008; Pouplier et al, 2011), although these fine phonetic differences may not be perceptible (Niebuhr and Meunier, 2011). Similarly, physiological studies of speech errors present evidence for gradual shifts between categories that may be perceived as clear instances of one category and may even result in auditory transcription errors (e.g., Pouplier and Hardcastle, 2005; Goldstein et al, 2007).…”
Section: Introductionmentioning
confidence: 99%